Surface science : an introduction - Hudson, John B. (Butterworth-Heinemann, 1992)
The whole field of surface science is covered in this work. Starting with a description of the structure and thermodynamics of clean surfaces, the book goes on to discuss kinetic theory of gases and molecular beam formation. This is followed by a large section on gas-surface interactions, and another major section on energetic particle-surface interactions. The final chapter provides the background to crystal nucleation and growth. The approach adopted is interdisciplinary and slanted towards the experimental side, with practical analytical techniques being used to illustrate general principles.